ChemInform Abstract: Carboxylates as Sources of Carbon Nucleophiles and Electrophiles: Comparison of Decarboxylative and Decarbonylative Pathways. Issue 10 (7th March 2013) - Dzik, Wojciech I.; Lange, Paul P.; Goossen, Lukas J.
Abstract Review: 78 refs.